Identification of Leptospira in water by Fe-Pd-doped polyaniline nanocomposite thin film - Abdullah, Huda; Mustaza, Seri Mastura; Bejo, Siti Khairani; Yahya, Iskandar; Kamal, Noorfazila; Othman, Mohd Hafiz Dzarfan (SAGE Publications, 2021)
Leptospirosis disease was caused by rat urine which contains the genus Leptospira bacteria. In this study, the fabrication of Pd-Fe-doped polyaniline nanocomposite thin films for the determination of the genus Leptospira bacteria thin films has been investigated. Pd-Fe-doped polyaniline nanocomposite thin films were fabricated by sol–gel spin coating method. The electrode sensors were immersed in the Leptospira solution. The resulting materials were investigated using field-emission scanning electron microscopy, atomic force microscopy, transmission electron microscopy, and current–voltage measurement. The atomic force microscopy images show the specific morphology films’ structure for Leptospira detection, whereas the field-emission scanning electron microscopy image shows the irregularity of clump nanoparticles in thin film surfaces. Transmission electron microscopy result shows that metal alloy (Fe-Pd) embedded in the polymer matrix. Current–voltage measurement with and without incubation of the thin film into Leptospira solution was done to show the relationship between concentration bacteria versus current. The result shows that polyaniline-Fe0.4-Pd0.6 nanocomposite thin film has higher sensitivity in detecting Leptospira, where it has performed with the highest percentage of the sensitivity of 16.9%. Besides that, selectivity tests were conducted to distinguish the existence of Leptospira, Pseudomonas aeruginosa, and Staphylococcus aureus bacteria. These results confirm the potentials of polyaniline metal alloys’ nanocomposite thin films to be used for Leptospira bacteria detection in water.